Essentials of radiographic physics and imaging - Johnston, James N; Fauber, Terri L (Elsevier, 2020)
Essentials of Radiographic Physics and Imaging, 3rd Edition follows the ASRT recommended curriculum and focuses on what the radiographer needs to understand to safely and competently perform radiographic examinations. This comprehensive text gives you a foundational understanding of basic physics principles, imaging principles, radiation production and characteristics, digital image quality, imaging equipment, digital image acquisition and display, image analysis, and more. Nakladatelská anotace. Kráceno.
Keywords: Physics; fyzika; radiografie; Radiography; diagnostické zobrazování; Diagnostic Imaging; radiologie, nukleární medicína a zobrazovací metody; Technology, Radiologic; radiologická technologie